A programme for empowering rural women : Considerations for social work education - Sathiparsad, R (Social Work/Maatskaplike Werk, 2002)
Women, specifically rural women, have often been discriminated against, undermined and disempowered with regard to their roles and their rightful places in society. The process of empowering women requires attitudinal change, gender sensitivity and the active promotion of dignity, self-esteem and the well-being of women. It is encouraging to note that the transformation process has resulted in conscious efforts being made to address the problems facing women and to improve the overall status of women. The White Paper for Social Welfare (1997) clearly acknowledges that, in addition to their roles in the family, women in rural communities contribute voluntary time to social and development programmes. However, they are disadvantaged by policies of the past which keep them isolated and deny them access to social and economic opportunities which could improve their lives. The document highlights the urgency of the need to build capacity and to promote the advancement of women at all levels in society via comprehensive and integrated services. In keeping with the needs outlined above, this paper presents a pilot programme implemented and evaluated with women in a rural area, Vulamehlo, situated to the south of Durban. Feedback from the participants relating to their experiences of the programme are discussed and some considerations for social work education are presented.